1969
DOI: 10.1115/1.3580158
|View full text |Cite
|
Sign up to set email alerts
|

Free Convective Flow Patterns in Cylindrical Annuli

Abstract: The results of nil available experimental investigations into the characteristics of free convective flow of air between horizontal isothermal concentric cylinders are reviewed and several discrepancies are pointed out. An experimental study is described which was directed at resolving these discrepancies and categorizing the several flow patterns which have been observed.Using six different cylinder sets and varying both the annulus pressure and temperature difference between the cylinder surfaces, a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
64
3
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 0 publications
18
64
3
1
Order By: Relevance
“…In the present numerical studies, the annulus radius ratios were selected to permit comparison of the numerical solutions with experimental results. The value of R l 1.6 employed in the moderate gap numerical study was also used in the experiments by Powe et al (1969). The radius ratio R l 2.2 was chosen for investigation of a large-gap annulus since it is close to the values R l 2.18 and R l 2.3 at which benchmark comparisons of the numerical solutions and experimental results are made.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present numerical studies, the annulus radius ratios were selected to permit comparison of the numerical solutions with experimental results. The value of R l 1.6 employed in the moderate gap numerical study was also used in the experiments by Powe et al (1969). The radius ratio R l 2.2 was chosen for investigation of a large-gap annulus since it is close to the values R l 2.18 and R l 2.3 at which benchmark comparisons of the numerical solutions and experimental results are made.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The classification of the annulus geometry considered in the present study as either moderate gap or large gap, depending on the radius ratio R, is based on the flow map of Powe, Carley & Bishop (1969) for air. Their experiments and compilation of experimental results from other investigators indicate that flow in large-gap annuli (R 1.71) remains stable up to much higher Rayleigh numbers than in moderate gap annuli (1.24 R 1.71).…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of theoretical analysis [7,8], experimental studies [9,10,11] and numerical calculations [12,13,14] of natural convection in this type of systems indicate that the main factors determining the intensity of fluid motion are: the geometry of the area and the temperature distribution on its edges. Therefore, in order to obtain possibly the widest range of the analyzed subject, the samples made of different elements were tested.…”
Section: Characteristics Of the Test Samplesmentioning
confidence: 99%
“…Bishop [13] and Powe et al [14] experimentally studied the natural convection in a closed helium filled annular space. Yoo [15] reported that when Rayleigh number was greater than a critical value, the stable solution was observed.…”
Section: Introductionmentioning
confidence: 99%